Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.20409/berj.2019.165
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Brand Equity and Perceived Value for Stimulating Purchase Intention in B2C e-Commerce Web Sites

Abstract: This paper attempts to clarify the underlying mechanism behind purchase decision on B2C e-commerce web sites. Research question of the study is to investigate the interaction between brand equity, perceived value and purchase intention in B2C ecommerce context by specifically questioning the direct and indirect effects within the process. Firstly, the hypotheses in the conceptual model were tested. Secondly, post-hoc analyses were conducted to clarify the mediator roles of perceived value and brand loyalty. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
0
17
0
3
Order By: Relevance
“…SJME 2.3 Brand loyalty Oliver (1999) defined brand loyalty as "a deeply held commitment to rebuy a preferred product or service consistently in the future, despite situational influences and marketing efforts having the potential to cause switching behaviour". Brand loyalty influences buying intention and word of mouth (Civelek and Ertemel, 2019). In the digital context, studies found a positive relationship between brand loyalty and brand experience (Gavurova et al, 2018), and between brand loyalty and financial performance (Narteh, 2018).…”
Section: Brand Lovementioning
confidence: 99%
“…SJME 2.3 Brand loyalty Oliver (1999) defined brand loyalty as "a deeply held commitment to rebuy a preferred product or service consistently in the future, despite situational influences and marketing efforts having the potential to cause switching behaviour". Brand loyalty influences buying intention and word of mouth (Civelek and Ertemel, 2019). In the digital context, studies found a positive relationship between brand loyalty and brand experience (Gavurova et al, 2018), and between brand loyalty and financial performance (Narteh, 2018).…”
Section: Brand Lovementioning
confidence: 99%
“…BAW is an imagination of a brand in the mind of a customer and the ability of the customer to recognize and recall a brand in various situations (Keller, 1993;Aaker, 1994). BAW is the ability of a brand to get recognized by customers before they make PI (Civelek and Ertemelb, 2019). Tariq et al (2017) concluded that BAW is highly significant for BE since it has strong relationship with PI.…”
Section: Brand Awarenessmentioning
confidence: 99%
“…Marketing in e-commerce depends on how marketers can measure customer satisfaction that can affect brand equity (Nasiruddin & Hashim, 2015). Brand equity becomes essential because it can influence positive attitudes that can manifest in consumer behavior, such as purchase intentions (Bae, Jung, Moorhouse, Suh, & Kwon, 2020;Civelek & Ertemel, 2019).…”
Section: Introductionmentioning
confidence: 99%